Musical Activity in The Music Learning Process Through Children Songs in Primary School Level - Sinaga, Syahrul Syah; Susanto, Susanto; Ganap, Victor; Rohidi, Tjetjep Rehendi (Harmonia: Journal of Arts Research and Education, 2018)
This study aims to analyze and describe the musical activity in the process of learning music through children songs in primary school. A qualitative approach in this research is made by focusing on the field research method. Data were collected by observation techniques, interviews, and documentation studies. Data analysis was done by following certain stages respectively, i.e. data collection, data reduction, data display, conclusion drawing, and verification. The results showed that musical activities implemented in three primary schools consist of (1) listening to music; (2) singing; (3) playing musical instruments; (4) moving to follow the music; and (5) reading music. However, forms, types, and variations of the musical activities taking place in these schools are different, depending on the schools’ policy, schools’ abilities, and music teachers’ abilities in teaching the music subject.